Geopolymers: Enhancing Environmental Safety and Sustainability in Construction - Aiman, Muhammad S.; Othman, Idris; Waqar, Ahsan; Hamah Sor, Nadhim; Isleem, Haytham F.; Najm, Hadee M.; Benjeddou, Omrane; Sabri, Mohanad Muayad Sabri (Salehan Institute of Higher Education, 2024)
This study underscores the significant environmental advantages of geopolymer, notably its capacity for substantial CO2emission reduction and sustainable waste management by repurposing industrial by-products, enhancing the environmental safety in oil and gas projects. Central to our investigation is the identification and strategic overcoming of critical obstacles to the broader application of geopolymer, aiming to bridge the gap between its recognized potential and practical implementation in construction practices. Through a comprehensive analysis involving pilot, main, and validation surveys among construction industry professionals, we employed exploratory factor analysis (EFA) and structural equation modeling (SEM) to elucidate the relationships between various barriers and the success of geopolymer concrete applications. Our findings reveal that standards and knowledge significantly influence the adoption of geopolymer concrete, with an R² value of 0.873 indicating a high predictive utility of these constructs. The research underscores the critical need for enhanced support in research and development to improve geopolymer concrete's durability and performance over time. Significantly, this study contributes novel insights into overcoming the industry's hesitancy towards geopolymer concrete, highlighting its importance for sustainable construction practices and reducing the environmental footprint of building materials. Doi: 10.28991/CEJ-2024-010-10-015 Full Text: PDF